2016
DOI: 10.2174/1745017901612010142
|View full text |Cite
|
Sign up to set email alerts
|

Does the “Silver Bullet” Lose its Shine Over the Time? Assessment of Loss of Lithium Response in a Preliminary Sample of Bipolar Disorder Outpatients

Abstract: Background:Though often perceived as a “silver bullet” treatment for bipolar disorder (BD), lithium has seldom reported to lose its efficacy over the time.Objective:The aim of the present study was to assess cases of refractoriness toward restarted lithium in BD patients who failed to preserve maintenance.Method:Treatment trajectories associated with re-instituted lithium following loss of achieved lithium-based maintenance in BD were retrospectively reviewed for 37 BD-I patients (median age 52 years; F:M=17:2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…Of note, two forms of acquired nonresponse to lithium that develop over the treatment course in patients who have previously shown adequate response have been reported. The first type of nonresponse is discontinuation-induced refractoriness, is when patients who have showed good long-term response to lithium then discontinue treatment, and after experiencing a major recurrence, do not respond to lithium at previously effective doses [ 38 ]. The second type of nonresponse is the development of a pharmacodynamic tolerance to lithium, described as mild, brief, or infrequent symptoms starting to occur then progressively increasing in severity, duration, or frequency, until the original pattern of illness prior to treatment recurs, even while maintaining lithium treatment [ 39 ].…”
Section: Guidelines To Initiating and Maintaining Lithiummentioning
confidence: 99%
“…Of note, two forms of acquired nonresponse to lithium that develop over the treatment course in patients who have previously shown adequate response have been reported. The first type of nonresponse is discontinuation-induced refractoriness, is when patients who have showed good long-term response to lithium then discontinue treatment, and after experiencing a major recurrence, do not respond to lithium at previously effective doses [ 38 ]. The second type of nonresponse is the development of a pharmacodynamic tolerance to lithium, described as mild, brief, or infrequent symptoms starting to occur then progressively increasing in severity, duration, or frequency, until the original pattern of illness prior to treatment recurs, even while maintaining lithium treatment [ 39 ].…”
Section: Guidelines To Initiating and Maintaining Lithiummentioning
confidence: 99%
“…However, there is general consensus that lithium has a certain degree of effectiveness in about 60% of patients, while it is ineffective in about 1/3 [5,6]. Additionally, loss of efficacy can be observed after discontinuation in patients previously showing a good response to the drug [7]. Lithium has also been shown to protect against mood switching [8].…”
Section: Introductionmentioning
confidence: 99%
“…Six case reports with a total of 11 patients and six naturalistic cohort studies including 403 patients were identified. In addition to those originally reviewed by de Vries ( 2013 ), we have included two further studies (Cakir et al 2017 ; Fornaro et al 2016 ) published subsequently. Furthermore, we uncovered a large-scale nationwide health care registry study assessing the efficacy of pharmacotherapy in individuals with bipolar disorder who had previously discontinued lithium (Holm et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%